Faktor-Faktor Yang Mempengaruhi Rendahnya Cakupan Pemeriksaan IVA Di Puskesmas Margorejo - Sri Wahyuni (Jurnal Ventilator, 2024)
Cervical cancer is very dangerous because it can result in death, so it needs serious attention. One of the efforts to prevent cervical cancer in women of fertile age (WUS) is by conducting a visual inspection of acetic acid (IVA) test. This study aims to determine the factors that influence the low number of IVA examinations at the Margorejo Pati Community Health Center. Cervical cancer is the fourth highest cancer in women with an estimated 570,000 new cases in 2018 which represents 6.6% of all female cancers. The high mortality rate from cervical cancer globally can be reduced through prevention, early diagnosis, effective screening and treatment programs. As of 2016, VIA coverage in Indonesia was 4.34%, which is still far from the national target of 10% at the end of 2015. In Indonesia, cervical cancer is still the cancer with the second largest number of sufferers after breast cancer. The incidence of new cases of cervical cancer according to GLOBOCAN data, 2018 for women in Indonesia is around 32,469 cases (17.2%) with a death rate of 18,279 (8.8%). The Global Burden of Cancer Study (Globocan) from the World Health Organization (WHO) noted that the total cancer cases in Indonesia in 2020 reached 396,914 cases and the total deaths were 234,511 cases. According to the Indonesian Cancer Foundation (YKI), one of the causes of the high number of cancer cases in Indonesia is environmental conditions that continue to produce carcinogens, such as cigarettes, processed meat, etc. Other causes that also influence include the habit of staying up late, lack of exercise, and eating too much. As a form of cancer prevention and control in Indonesia, especially breast cancer and cervical cancer, the Ministry of Health has made several efforts such as early detection of breast cancer and cervical cancer in women aged 30-50 years using the Visual Inspection method with Acetic Acid (IVA).